The Role and Challenges of Religious Teachers in Learning Technology in the 21st Century - N, Zulkifli; Kuswandi, Dedi; Aulia, Fikri (Mau`izhah : Jurnal Kajian Keislaman, 2023)
Today technological sophistication is growing rapidly, especially in the world of education so that it provides challenges and roles for educators in the learning process, one of which is about religious learning. Religion is a very important foundation in education. Therefore, educators must be able to develop skills in education that are collaborated with technological sophistication products. This study aims to find out how the role and challenges faced by religious teachers in 21st century learning technology. The research method used by researchers is a quantitative method using online-based questionnaires. The research was conducted on teachers who in fact taught Islamic religious education. The research was conducted by providing several questions through the help of Google Form, and the research was conducted online. The result of this study is to find out how important the role of technology in the 21st century is for religious teachers so that religious teachers do not stutter in technology or outdated to the technological developments that appear today. The conclusion of this study explains that in the 21st century the role and challenges of religious teachers in using learning technology are very influential on the teaching and learning process. The limitation of this study is that researchers do not observe directly into the field so that they do not maximally know how the role and challenges faced by religious teachers in 21st century learning technology, therefore researchers hope that further researchers can observe directly into the field so that they can maximally explain the role and challenges faced by religious teachers regarding technology in the 21st century learning process.